KI67 IMMUNOSTAINING'S DIAGNOSTIC AND PROGNOSTIC SIGNIFICANCE IN GESTATIONAL TROPHOBLASTIC DISORDERS: A RETROSPECTIVE STUDY. : JPUMHS;2024:14:04,50-59.http://doi.org/10.46536/jpumhs/2024/14.04.560 - Sana Ullah Khan1, Zarmeena Liaqat2, Faiqa Mubeen3, Iqra Shams4, Falak Naz5, Shafaq Saleem6 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
ABSTRACT: BACKGROUND: Gestational trophoblastic diseases GTDs are rare gynecological disorders caused by abnormal trophoblastic progression. Subtypes include complete moles, partial moles, and hydropic abortions frequently share physical characteristics, challenging diagnosis. Ki67, a nuclear proliferation marker, has emerged as a viable tool for improving diagnostic accuracy and determining prognosis. OBJECTIVE: The aim of this study is to examine the diagnostic and prognostic impact of Ki67 immunostaining for classifying GTD subtypes and predicting high-risk patients, such as persistent trophoblastic disease PTD and choriocarcinoma. METHODOLOGY: A retrospective descriptive study was carried out from January to December 2023 in Lady Reading Hospital, Peshawar. In terms of 1,012 placental biopsy samples, 197 19.5% were diagnosed with GTDs, comprising 150 complete moles, 45 partial moles, and two unusual cases of choriocarcinoma and enhanced placental site reactivity. Fifty cases were chosen for Ki67 immunostaining. Staining intensity 0 to 3+ and extent 0 to 4+ were evaluated and classified, and statistical analyses were done to link findings to clinical outcomes. RESULTS: In 85% of cases complete moles revealed high 3+ Ki67 staining, with 70% showing a diffuse >50% extent. Partial moles showed moderate 2+ staining in 33.3% cases. However, hydropic abortions were primarily negative. All PTD and choriocarcinoma cases had significant and diffused Ki67 staining. CONCLUSION: Ki67 immunostaining is an effective technique for distinguishing GTD subtypes and detecting high-risk cases. Its integration into standard diagnostic techniques, combined with supporting markers, has the potential to improve GTD management, particularly in resource constrained settings.